Pharmacotherapy for obesity 2 - pharmacological agents in current use & under development - Proietto, Joe (Henry Stewart Talks, 2018)
Clinical studies involving pharmacological drugs for the treatment of obesity, Phentermine, Topiramate, Phentermine plus topiramate, Orlistat, Liraglutide, Lorcaserin, Naltrexone plus bupropion, Semaglutide, Pramlintide, Metreleptin, Pramlintide plus metreleptin, Beloranib, Combination of hormones